Biometria e bioimpedância in vivo como alternativas para predição dos componentes químicos e teciduais de cordeiros - Moro, Anderson Bortoluzzi (2016)
Bioimpedance (BIA) is a method that applies the impedance of technology in the study of body composition by evaluating the difference of electric conductivity of the tissues. The BIA results are expressed by primary measures resistance (R) and reactance (Xs). The study aimed to propose equations that can estimate the chemical and tissue carcass components using in vivo BIA in lambs slaughtered at different slaughter weights. The experiment was conducted at sheep breeding laboratory of the Universidade Federal de Santa Maria, Santa Maria, RS. Were used 31 uncastrated lambs, crossbreed Texel versus Ile de France, with about age 3 months and 19.7 kg of average live weight. Lambs were feedlot fed ad libitum with a standard diet.The predefined slaughter weights were 20, 26, 32 and 38 kg live weight . A day before the slaughter was made in vivo assessments and, after 14 hours fasting were made in vivo BIA measurements. It was used monofrequencial apparatus, alternating current generator of 50 kHz and 800 uA. This device has 4 electrode terminals. The electrode placement were on the animal right side, on the ventral region, 10 cm between the electrodes transmitters and receivers. The electrodes used were acupuncture needles. After slaughter were made assessments on carcass. In the right half carcass were made deboning to obtain the tissue and chemical components. Correlation analyzes were used to determine the variables included in the regression analyzes. Multiple regression analysis with stepwise control were performed using the carcass components as dependent variables and measurements from in vivo assessments, in vivo BIA, carcass assessments and their combinations as predictors parameters. The resistive density (DRs) and reactive density (DXc) bioelectric volume (V) and phase angle (AF) were the best BIA variables correlated to carcass body constituents. The prediction equations using measurements BIA showed R2 0.84 and 0.93, for bone and soft mass (kg), respectively. R2 0.73, 0.84, 0.87 and 0.91, respectively, ash, moisture, lipids and protein (kg). And R2 0.76, 0.89 and 0.90 respectively to lipids protein ratio, soft mass without fat and lean body mass (kg). The BIA in vivo has good potential to estimate chemical and tissue carcass composition of lambs slaughtered at different slaughter weights. The BIA was more accurate estimating the absolute body components than percentage carcass components.